Evaluate the expression when \[ a=4 \text { and } b=7 \] \( 2 a^{2}-4 b-4 a(b-a)=[?] \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
Let's evaluate the expression step by step with the values \( a = 4 \) and \( b = 7 \): 1. Calculate \( a^2 \): \[ a^2 = 4^2 = 16 \] 2. Substitute \( a \) and \( b \) into the expression: \[ 2 a^{2} - 4 b - 4 a (b - a) \] 3. Substitute the values: \[ 2 \cdot 16 - 4 \cdot 7 - 4 \cdot 4 \cdot (7 - 4) \] 4. Simplify each term: \[ 2 \cdot 16 = 32 \] \[ 4 \cdot 7 = 28 \] \[ 7 - 4 = 3 \quad \text{so} \quad 4 \cdot 4 \cdot 3 = 48 \] 5. Combine all parts: \[ 32 - 28 - 48 \] 6. Calculate stepwise: \[ 32 - 28 = 4 \] \[ 4 - 48 = -44 \] So, the value of the expression when \( a = 4 \) and \( b = 7 \) is \[ \boxed{-44}. \]